Improvement of Literacy, Numeracy and Life Skills of "Sanggar Belajar" Students in Malaysia - Nur Azizah, Siti; Mumfaza, Rizqia; Ahsanu Amala, Rizkika; Roisah, Roisah; Hanindita Agustin, Valya; Nurmelinia, Nurmelinia; Safitri, Farida; Hidayah, Nurul (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2023)
Teachers have an essential role and majorly influence the quality of learning. The SB Hulu Kelang and At-Tanzil Kg Lindungan are new learning centers with limited teachers. The teacher's skills in stimulating the development of children's literacy, numeracy, and life skills are limited, even though these three components are needed in this digital era. This international partnership community service (PKM-KI) aims to strengthen Teacher Skills in Stimulating the Development of Literacy, Numeracy, and Life Skills at the SB Hulu Kelang and At-Tanzil Kg Lindungan, Selangor, Malaysia. This PKM K-I service involved one lecturer and seven students. The method of implementing community service is carried out through several stages, namely, (1) initial mapping of partners' conditions, equalization of perceptions and coordination of partner problems, (2) debriefing for students about stimulating literacy, numeracy, and life skills in children, then practical students, (3) mentoring by the service team to students and teachers regarding literacy, numeracy, and life skill stimulation techniques, (4) students were deployed to the location to provide practical examples of teaching literacy, numeracy, and life skills to children (5) the teacher accompanied by the service team observed the learning process carried out by students, (6) the teacher applies various teaching methods, (7) the results of the application are evaluated for further learning improvement. The conclusion from the dedication shows that the understanding & pedagogical skills of SB Hulu Kelang and At-Tanzil Kg Lindungan teachers have increased. SB Hulu Kelang and At-Tanzil Kg Lindungan teachers can apply Best Practices, use learning innovations and modeling techniques, and integrate technology in learning that has never been done before. Students are delighted because the teacher delivers literacy, numeracy, and life skill activities in a fun, easy, and exciting way and challenges children's understanding.